Justice in assistance: a critique of the ‘Singer Solution’ - Blunt, Gwilym David (Journal of global ethics, 2015)
This article begins with an examination of Peter Singer's ‘solution’ to global poverty as a way to develop a theory of ‘justice in assistance.’ It argues that Singer's work, while compelling, does not seriously engage with the institutions necessary to relieve global poverty. In order to realise our obligations it is necessary to employ secondary agents, such as non-governmental organisations, that produce complex social relationships with the global poor. We should be concerned that the affluent and their secondary agents are complicit with unjust institutions or can be the source of injustice. What is needed is a theory of justice in assistance. This is a distinct area of justice theory because these agents are not primary agents, like states, but they often provide the basic social goods that we associate with primary agents. The article ends by putting forward a provisional conception of justice in assistance based on the republican idea of non-domination.